DIMENSI OLIGOPSONISTIK PASAR DOMESTIK CABAI MERAH - HUTABARAT, BUDIMAN; RAHMANTO, BAMBANG (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
The oligopsonistic market with high potential and persistent growth in domestic demand and supply has partly led the supply-side government policies in the form of extensification and intensification program of chilli to be ineffective to pursue the objective of improving farmer’s welfare. The paper is intended to investigate marketing performance and system through its elements, namely market chain, number and share of maarket agents, agent market power. It concludes that farmer receives the least returns relative to others. The wholesale trader seems to have strong influence in price discovery. Given the circumstances, the government support is called for dissolving the oligopsonistic power of the wholesaler.
Keywords: Oligopsonistic, Supply-side, Marketing Channel, Price Formation.